Soil properties improvement and use of adaptive plants for land rehabilitation of post tin mining closure in Bangka Island, Indonesia - Pratiwi; Budi Hadi Narendra; Budi Mulyanto (Society for Indonesian Biodiversity, 2020)
Abstract. Pratiwi, Narendra BH, Mulyanto B. 2020. Soil properties improvement and use of adaptive plants for land rehabilitation of post tin mining closure in Bangka Island, Indonesia. Biodiversitas 21: 505-511. Indonesia is still facing several environmental problems due to improper mining activities, such as tin mining activities in Bangka island. The area of post tin mining closure in this island has left tailing area over unstructured overburden. This condition causes infertile land, which is indicated by low physical, chemical, and biological soil properties for supporting plant growth. Therefore, amelioration material is needed to increase soil fertility in rehabilitating this area. The purposes of the study are to improve soil properties and the use of adaptive plants for land rehabilitation of post tin mining closure. The observation was carried out on plots with ameliorant materials treatment, and no treatment as a control plot. Adaptive plants used are trembesi (Samanea saman), sengon buto (Enterolobium cyclocarpum), and ampupu (Eucalyptus urophylla); while ameliorant materials were mixture of overburden materials, NPK fertilizer, lime (dolomite), topsoil material, and compost, with proportion 49%, 1%, 10%, 20%, 20% of media weight respectively. The results showed that three years after planting, ameliorant treatment plots showed growth percentage of E. urophylla, E. cyclocarpum, and S. saman as 96.1%, 73.4%, and 52.4% respectively, while in the control plots were 94.1%, 93.8%, and 35.0% respectively. The ameliorant treatment plots as compared to control plots, showed a significantly different effect on the growth parameters, both height and diameter for S. saman and E. cyclocarpum, while for E. urophylla, although the ameliorant treatment showed better growth parameters, but the differences were not significant.